A probability metrics approach to financial risk measures [electronic resources] - Rachev, S. T. [ (Svetlozar Todorov)]; Fabozzi, Frank J.; Stoyanov, Stoyan V. (Wiley-Blackwell, 2011)
"A Probability Metrics Approach to Financial Risk Measures relates the field of probability metrics and risk measures to one another and applies them to finance for the first time. Helps to answer the question: which risk measure is best for a given problem? Finds new relations between existing classes of risk measures. Describes applications in finance and extends them where possible. Presents the theory of probability metrics in a more accessible form which would be appropriate for non-specialists in the field. Applications include optimal portfolio choice, risk theory, and numerical methods in finance. Topics requiring more mathematical rigor and detail are included in technical appendices to chapters." -- Provided by publisher